Epidemiological Study of Wasting Among Children Under Five in Coastal Areas: An Analysis of Food Security and Dietary Quality - Yamin, Imam Syahputra; Rahmawati, Santi Deliani (PT. LARPA JAYA PUBLISHER, 2026)
Coastal regions are typically associated with abundant access to animal protein; however, empirical data reveal a high prevalence of wasting in these areas, presenting a coastal nutritional paradox. Despite being the urban center of West Nusa Tenggara, Mataram City faces a significant burden of wasting, particularly within its coastal communities. This study aimed to analyze the association between household food security, dietary patterns, and the incidence of wasting. A cross-sectional study was conducted in Mataram City from February to September 2024, involving 155 children aged 12–59 months selected via total sampling. Food security was assessed using the Household Food Insecurity Access Scale (HFIAS), while dietary patterns were evaluated using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Nutritional status was determined via anthropometric measurements (weight-for-height). The results indicated an alarming prevalence of wasting (49.7%) and severe wasting (20.0%). Although 52.3% of households experienced moderate food insecurity, statistical analysis revealed no significant association between household food security and wasting (p=0.659). Conversely, dietary patterns were significantly associated with wasting (p=0.003). This study highlights a paradox wherein household food access does not guarantee optimal child nutritional status. The primary driver of wasting in this coastal population appears to be poor dietary quality and insufficient protein intake rather than mere food availability. Future interventions must shift from generalized food aid to targeted nutritional education focusing on dietary diversity.